Hydroalcoholic extract of Withania somnifera leaf and α-tocopherol acetate in diets containing oxidised oil: effects on growth performance, immune response, and oxidative status in broiler chickens. Issue 1 (14th December 2020) - Azimi, Vahid; Mirakzehi, Mohammad Taher; Saleh, Hassan
Abstract: This study was conducted to evaluate the effects of hydroalcoholic leaf extract of Withania somnifera ( WS ) and α-tocopherol acetate (α-Toc) in the diets containing oxidised oil on the growth performance, immune response, and oxidative status in the broiler chickens. A 3-way factorial design (2 × 3 × 2) was applied consisting of the oxidised oil (0 and 2%), WS (0, 100 and 200 mg/kg diet), and α-Toc (0 and 200 mg/kg). In total, 600 one-day-old male broilers were randomly subjected to 12 treatments with 5 replicates (10 birds/replicate). Broilers were provided with feed and water ad libitum during the 42-day experimental period. On day 42, one bird per each replicate was killed to measure the lymphoid organ weights, intestinal morphometric parameters, and MDA content in the thigh meat. Dietary oxidised oil reduced the FI, and BWG ( p  < .05). In contrast, dietary WS at a concentration of 200 mg/kg alleviated the negative effects of the oxidised oil on the BWG. Birds fed with the dietary oxidised oil revealed lower titres of antibody against the SRBC ( p  < .05). Antibody titres were significantly increased by the supplementary WS ( p  < .05), except for IgG, and IgM during primary and secondary responses, respectively. Dietary supplementation of WS at the concentrations of 100 or 200 mg/kg resulted in a higher CBH response after 12 h ( p  < .01). Birds fed with the diet supplemented with WS exhibited significantly higher spleen weight than those fed with the non- WS -supplemented diets ( p  < .01). Dietary oxidised oil significantly increased the MDA content in thigh meat, and inversely reduced the activity of serum antioxidant enzymes ( p  < .05). Birds fed with the WS -supplemented diets showed significantly lower levels of MDA content in thigh meat, and conversely higher values of serum GPx and SOD activities ( p  < .05). The GPx activity values were significantly higher for the birds fed with the dietary α-Toc compared to those fed with the non- α-Toc-supplemented diets ( p  < .05). Our findings showed that the presence of WS in the broilers diets as an alternative to α-Toc could be a good approach to improve the performance, immune response, and meat oxidative stability under oxidative stress conditions. Highlights: Dietary oxidised oil reduced the FI, and BWG, and the diets supplemented with WS leaf extract alleviated the deleterious effects of the oxidised oil on the BWG. Dietary WS revealed the immunostimulatory effects. The birds fed with the WS -supplemented diets showed a higher antibody titre against the SRBC. Dietary inclusion of WS in the broilers diets negated the negative effects of the oxidised oil by reducing the MDA content in thigh meat and increasing the activity of the antioxidant enzymes.